Resurrected Bodies: Individual Experiences and Collective Expressions of Organ Transplant in North America - MacDonald, Arlene (Bulletin for the study of religion, 2010)
The anthropological literature on transplant, though theoretically and ethnographically rich, does not address religion in any substantial way. And while bio-ethical considerations of transplant regularly address religion, treatments are generally circumscribed to a list of various faith traditions and their stance toward organ transplant. Such a presentation reduces "religion" to the world’s recognized faith traditions, "religious actors" to the official spokespersons of these traditions, and "religious belief" to moral injunctions. The objective of the thesis was to illuminate the prominent place of religion in the lived experience of transplant recipients and donors, in the public policy and professional activities of transplant officials, and in the transplant discourses of North America